Recycling tenofovir in second-line antiretroviral treatment with dolutegravir: outcomes and viral load trajectories to 72 weeks - Keene, Claire M (J Acquir Immune Defic Syndr, 2023)
BACKGROUND: Recycling tenofovir and lamivudine/emtricitabine with dolutegravir (TLD) after failure of non-nucleoside transcriptase inhibitor (NNRTI) first-line antiretroviral therapy (ART) is more tolerable and scalable than dolutegravir plus optimized nucleoside reverse transcriptase inhibitors. Studies have demonstrated TLD’s efficacy as second-line, but long term follow-up is limited. METHODS: ARTIST is a single arm, prospective, interventional study conducted in Khayelitsha, South Africa, which switched 62 adults with two viral loads (VL) >1000 copies/mL from tenofovir, lamivudine/emtricitabine and an NNRTI to TLD. We report efficacy to 72 weeks and, in a post hoc analysis, evaluated VL trajectories of individuals with viraemic episodes. RESULTS: Virologic suppression was 86% (95% Confidence Interval (CI) 74-93), 74% (95% CI 61-84) and 75% (95% CI 63-86) <50 copies/mL, and 95%, 84% and 77% <400 copies/mL at week 24, 48 and 72 respectively, with 89% (50/56) resistant (Stanford score ≥15) to tenofovir and/or lamivudine pre-switch. No participants developed integrase-inhibitor resistance. Of the 20 participants not suppressed at week 24 and/or 48, two developed virologic failure, one switched regimen (adverse event), two were lost to follow-up, one missed the visit, one transferred out, nine resuppressed <50 copies/mL with enhanced adherence counselling and four remained viraemic (three with <200 copies/mL) at week 72. CONCLUSIONS: Recycling NRTIs with dolutegravir was effective for most participants to 72 weeks. Most with viraemia did not develop virologic failure and subsequently suppressed with enhanced adherence counselling or continued to have low-level viraemia. No integrase-inhibitor resistance was detected despite low-level viraemia in a minority of participants.